1998
DOI: 10.1046/j.1365-2052.1998.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Asian water buffalo (Bubalus bubalis): mitochondrial DNA D‐loop and cytochrome b sequence variation

Abstract: Swamp and river buffalo mitochondrial DNA (mtDNA) was sequenced for 303 bp of the cytochrome b gene for 54 animals from 14 populations, and for 158 bp of the D-loop region for 80 animals from 11 populations. Only one cytochrome b haplotype was found in river buffalo. Of the four haplotypes identified in swamp buffalo, one found in all populations is apparently ancestral both to the other swamp haplotypes and to the river haplotype. The phylogenetic relationships among the 33 D-loop haplotypes, with a cluster o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
3
7

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(117 citation statements)
references
References 27 publications
7
100
3
7
Order By: Relevance
“…The mtDNA cyt b gene was selected as template for DNA amplification because it had been used in species identification and in taxonomic and phylogenetic studies (Cook, Wang, & Sensabaugh, 1999;Irwin, Kocher, & Wilson, 1991;Kocher et al, 1989;Kuwayama & Ozawa, 2000;Lau et al, 1998;Su, Wang, Lan, Wang, & Zhang, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…The mtDNA cyt b gene was selected as template for DNA amplification because it had been used in species identification and in taxonomic and phylogenetic studies (Cook, Wang, & Sensabaugh, 1999;Irwin, Kocher, & Wilson, 1991;Kocher et al, 1989;Kuwayama & Ozawa, 2000;Lau et al, 1998;Su, Wang, Lan, Wang, & Zhang, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…E-mail: david.machugh@ucd.ie. ification) established taxonomic categorizations based on morphology, i.e., that between humped and humpless cattle and that between river and swamp buffalo (4,(12)(13)(14). The division in pigs is also between European samples and those from Asia (8,15).…”
Section: Diversity Capture and Genetic Inertiamentioning
confidence: 99%
“…The nucleotide variations in the D-loop region have been studied to reveal the genetic variation in, and population structure of, the chum salmon (Park et al 1993), the dunlin (Wenink and Baker 1996), the green turtle (Encalada et al 1996), the kokanee (Taylor et al 1997), the Japanese sika deer (Nagata et al 1998), the Asian water buffalo (Lau et al 1998), the Japanese golden eagle ) and the eastern lowland gorilla (Saltonstall et al 1998). Only four nucleotide differences were found among 16 chum salmon individuals (Park et al 1993), while 33 haplotypes were identified among 80 water buffalo individuals (Lau et al 1998). In comparison with the frequencies of haplotypes in the natural population of these vertebrates, that of the captive Oriental white storks (nine haplotypes among 26 individuals), can be considered relatively high.…”
Section: Resultsmentioning
confidence: 99%